A Comparative Studies of Cascaded Multilevel Inverters Having Reduced Number of Switches with R and RL-Load - Lipika Nanda; Abhijit Dasgupta; Ullash Kumar Rout (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Multilevel inverter offers many benefits for high power application compavered to conventional cascaded Multilevel Inverter topology.This paper presents Symmetric CMLI using variable frequency carrier based pulse width modulation techniques. The proposed topology reduces total harmonic distortion and reduced switching losses for seven level inverter. The simulation study of the proposed topology has been carried out in MATLAB/SIMULINK. The main objective of this paper is to achieve number of levels of MLI with reduced number of switches and DC power sources compared to conventional topology.